Microbial Removals by a Novel Biofilter Water Treatment System - Wendt, Christopher (Am J Trop Med Hyg, 2015)
Two point-of-use drinking water treatment systems designed using a carbon filter and foam material as a possible alternative to traditional biosand systems were evaluated for removal of bacteria, protozoa, and viruses. Two configurations were tested: the foam material was positioned vertically around the carbon filter in the sleeve unit or horizontally in the disk unit. The filtration systems were challenged with Cryptosporidium parvum, Raoultella terrigena, and bacteriophages P22 and MS2 before and after biofilm development to determine average log reduction (ALR) for each organism and the role of the biofilm. There was no significant difference in performance between the two designs, and both designs showed significant levels of removal (at least 4 log(10) reduction in viruses, 6 log(10) for protozoa, and 8 log(10) for bacteria). Removal levels meet or exceeded Environmental Protection Agency (EPA) standards for microbial purifiers. Exploratory test results suggested that mature biofilm formation contributed 1–2 log(10) reductions. Future work is recommended to determine field viability.